Efficient problem-solving method to relieve psychological stress in a sample of battered married women in central governorate of the Gaza Strip - Al-Saud, Asma Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The aim of the study was to determine the effectiveness of the problem-solving method in alleviating psychological stress in married victims of marital violence. The researcher selected a physical sample of 12 married female victims of violence at the Breij Women's Health Centre who were experiencing psychological stress as a result of violence. They also received the highest scores on the spousal violence scale and were deliberately selected. She used the semi experimental (single design) method with a single sample and applied the method without using a control group. She used a number of tools which are, the Spousal Violence Scale prepared by the researcher and the Cohen Psychosocial Stress Scale She developed a problem-solving model for use in alleviating psychological stress in battered married women and used a number of statistical methods that fit the study's questions and hypotheses. The study resulted in the presence of differences between the average ranks of the experimental group women on the pre and post application of the marital violence scale, there are differences between the average rank of women in the experimental group on the pre – and post- application of the psychologyical pressure scale. One of the main recommendations of the study was to activate the role of specialized institutions for battered married women through the implementation of individual and group guidance programmes to equip them with appropriate skills and strategies to contribute to positive adjustment.
Keywords: Problem; solving method; Psychologyical stress; battered married women